Policy distortions in the segmented rice market - Rakotoarisoa, Manitra A. (International Food Policy Research Institute, 2006)
High production and export subsidies in developed countries and high protection in both developed and developing countries have distorted rice trade. This study estimates the impact of rice policy distortions on developing countries’ rice production and trade potential. Because rice markets are highly segmented, major rice types are differentiated to estimate the impact of current and likely policy reforms. Analysis in long-grain, high-quality rice focuses on rice import and export markets in Latin America and shows that reduction of direct and implicit export subsidies in the US will benefit regional suppliers such as Argentina and Uruguay. Analysis of Indonesia’s import market of ordinary long-grain rice, where protection is high, reveals that tariff hikes in this large importing country are in part a response to increased support from the exporting side. Level of domestic stocks also determines tariff movements. In the short/medium grain rice market, this study focuses on the highly supported and protected rice market in Japan and find that only aggressive rates of increase in import tariff-rate quota and reduction in production subsidies would have significant impact on import volume and price. Prices and trade would also be affected by a reduction of the high over-quota tariff.